Le stage de terrain : que transmet-on en tant qu’enseignant chercheur ? - Camille Vergnaud; Julie Le Gall (Carnets de Géographes, 2017)
Considered as a place, an object of study, and a method, field work plays a significant role in higher education students training. But this important step in geography curriculum is still not often explained in detail from a pedagogical perspective. What is field work useful for? What does it mean to learn field work and to teach field work in an explicit way or a non-voluntarily one? This article is based on a fieldwork experience in Mexico in 2013 with 18 students from the Ecole Normale Supérieure de Lyon, as part of the research project named SELINA. This paper shows that fieldwork training is not only a tool to teach methods and an opportunity to train students in a different context, it is also a moment of mutual thinking about the working conditions and the professional identity of the academics.